Non-pharmacological interventions for vascular health and the role of the endothelium - Samuel R. C. Weaver; Catarina Rendeiro; Rebekah A. I. Lucas; N. Timothy Cable; Tom E. Nightingale; Helen M. McGettrick; Samuel J. E. Lucas (European Journal of Applied Physiology, 2022)
The most common non-pharmacological intervention for both peripheral and cerebral vascular health is regular physical activity (e.g., exercise training), which improves function across a range of exercise intensities and modalities. Numerous non-exercising approaches have also been suggested to improved vascular function, including repeated ischemic preconditioning (IPC); heat therapy such as hot water bathing and sauna; and pneumatic compression. Chronic adaptive responses have been observed across a number of these approaches, yet the precise mechanisms that underlie these effects in humans are not fully understood. Acute increases in blood flow and circulating signalling factors that induce responses in endothelial function are likely to be key moderators driving these adaptations. While the impact on circulating factors and environmental mechanisms for adaptation may vary between approaches, in essence, they all centre around acutely elevating blood flow throughout the circulation and stimulating improved endothelium-dependent vascular function and ultimately vascular health. Here, we review our current understanding of the mechanisms driving endothelial adaptation to repeated exposure to elevated blood flow, and the interplay between this response and changes in circulating factors. In addition, we will consider the limitations in our current knowledge base and how these may be best addressed through the selection of more physiologically relevant experimental models and research. Ultimately, improving our understanding of the unique impact that non-pharmacological interventions have on the vasculature will allow us to develop superior strategies to tackle declining vascular function across the lifespan, prevent avoidable vascular-related disease, and alleviate dependency on drug-based interventions.

Localised cutaneous microvascular adaptation to exercise training in humans - Ceri L. Atkinson; Howard H. Carter; Dick H. J. Thijssen; Gurpreet K. Birk; N. Timothy Cable; David A. Low; Floortje Kerstens; Iris Meeuwis; Ellen A. Dawson; Daniel J. Green (European Journal of Applied Physiology, 2018)

Do acute effects of exercise on vascular function predict adaptation to training? - Ellen A. Dawson; N. Timothy Cable; Daniel J. Green; Dick H. J. Thijssen (European Journal of Applied Physiology, 2018)

Effect of unilateral forearm inactivity on endothelium-dependent vasodilator function in humans - Gurpreet K. Birk; Ellen A. Dawson; N. Timothy Cable; Daniel J. Green; Dick H. J. Thijssen (European Journal of Applied Physiology, 2013)

Time course of arterial remodelling in diameter and wall thickness above and below the lesion after a spinal cord injury - Dick H. J. Thijssen; Patricia C. E. De Groot; Arne van den Bogerd; Matthijs Veltmeijer; N. Timothy Cable; Daniel J. Green; Maria T. E. Hopman (European Journal of Applied Physiology, 2012)